2006
DOI: 10.1002/ijc.22016
|View full text |Cite
|
Sign up to set email alerts
|

Benign ovarian cysts and breast cancer risk

Abstract: Benign ovarian cysts have been suggested to influence breast cancer risk. To provide a comprehensive picture of the relation between ovarian cysts and breast cancer, we analyzed the data of 3 case-control studies conducted in northern Italy and the Swiss Canton of Vaud between 1983 and 2001. These studies included 6,315 incident, histologically confirmed breast cancer cases and 6,038 hospital-based controls. Odds ratios (OR) and the corresponding 95% confidence intervals (CI) were estimated using unconditional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“…Consistent with recent reports from two other large studies [4,5], we observed significant inverse associations between a reported diagnosis of ovarian cysts and breast cancer. However, in the present study the evidence for an association was stronger in African Americans than in Caucasians.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with recent reports from two other large studies [4,5], we observed significant inverse associations between a reported diagnosis of ovarian cysts and breast cancer. However, in the present study the evidence for an association was stronger in African Americans than in Caucasians.…”
Section: Discussionsupporting
confidence: 92%
“…An OR of 0.71 (95% CI 0.61-0.81) was observed for a reported diagnosis of ovarian cysts and the result was consistent across study sites and was also consistent Data from the Women's CARE Study are consistent with the two recent pooled analyses in that all the OR estimates were less than 1.00. The results for the African American women are quite similar to the recent pooled analyses [4,5]. Although the OR estimates for ovarian cysts in Caucasians were also less than 1.0 in all subgroups, the effect was not significant or was marginally significant except for the significant OR of 0.85 (95% CI 0.76-0.96) among all Caucasians combined.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…A few reports have suggested an inverse association between benign ovarian cyst and breast cancer risk [51][52][53]. The mechanism is unknown, but there is an evidence of decreased breast cancer risk associated with oophorectomy for ovarian cysts [54,55].…”
Section: Benign Ovarian Cystsmentioning
confidence: 99%
“…Benign breast disease is characterized by irregular menstrual cycles and is more common at the end of reproductive life (1). Irregular cycles cause cystic disease in the breasts and ovaries and women with cystic ovarian disease therefore have a lower incidence of breast cancer (30).…”
Section: Introductionmentioning
confidence: 99%